Dogs, Strollers and Secret Courtyards. Preschool Tactics for Claiming Space in the Dense City - Danielle Ekman Ladru; Katarina Gustafson (Barn)
This article focuses on how inner-city preschools in Stockholm that do not have their own preschool yards, or only have a small enclosure, organise and perform everyday outdoor activities in a dense urban environment. Based on participant observations and interviews in two preschools with different spatial conditions, we analyse how finding urban space for preschool activities is an ongoing challenge due to the scarcity of spaces suitable for preschool groups. We show how preschool groups engage in tactical manoeuvres to find ways to claim spaces for themselves and how this involves a competition over space between different preschools.